Effect of collisionality dependence of thermal force on impurity transport under a lower collisional condition in DEMO scrape-off layer plasma. (18th March 2020) - Homma, Yuki; Hoshino, K.; Yamoto, S.; Tokunaga, S.; Asakura, N.; Sakamoto, Y.
Abstract: A preceding study (Homma et al 2018 Contrib. Plasma Phys . 58 629–37) presented an advanced model for thermal force whose applicable condition is extended from collisional to relatively low collisional plasma. According to this extended model, the thermal force reduces when plasma collisionality decreases. In the present study, the extended thermal force model has been implemented into a SOL-divertor integrated simulation code SONIC, in order to study the impact on impurity transport in DEMO-relevant scrape-off layer (SOL) plasma, due to thermal force reduction. A set of test simulations has been carried out supposing a reference steady-state operation scenario of the Japanese DEMO fusion reactor concept (JA DEMO). The thermal force has reduced by as much as 20%–70%, reflecting relatively lower collisionality in DEMO SOL plasma. The simulation results have demonstrated that the introduction of the collisionality dependence of thermal force leads to as much as 20%–80% of effective decrease in impurity density and its content ratio widely over the SOL upstream area under the DEMO relevant condition. Compared to the case with the conventional thermal force model, relative change rate of impurity content at representative poloidal positions are as follows: low-field side (LFS) X-point  −59%, poloidal top area  −22%, HFS upstream area up to  −80%, and no major impact around LFS upstream.